Multiple perspectives on integrated management systems and corporate sustainability performance - Gianni, Maria; Gotzamani, Katerina; Tsiotras, George (Journal of cleaner production, 2017)
The objective of this research is to concurrently address two identified gaps. Firstly, integrated management systems (IMS) are managed yet not measured and, secondly, corporate sustainability (CS) is measured yet not managed. It is argued that CS and IMS share stakeholder orientation, innovativeness and complexity. In light of the commonalities and opposing deficiencies, potential synergies are investigated to the mutual benefit of management systems integration and corporate sustainability. On the one side, integrated management systems may provide the necessary holistic framework for the management of corporate sustainability. On the other side, triple bottom line sustainability accounting and reporting may offer the metrics for IMS effectiveness. This reciprocating approach may aid both academics and practitioners to enhance the IMS positive impact and improve management of corporate sustainability. To serve the research purpose, a content analysis is performed drawing on three managerial theories. Resource, stakeholder and institutional theories are used to delve into the IMS and CS concepts and their relationships. Certain research propositions are generated and a framework is composed. Three key constructs - IMS resources, IMS level and CS performance - are conceptualised. The proposed framework can be subject to empirical validation in the future.